Genetic changes in beef cow traits following selection for calving ease. Issue 1 (27th January 2021) - Bennett, Gary L; Thallman, Richard M; Snelling, Warren M; Keele, John W; Freetly, Harvey C; Kuehn, Larry A
Abstract: One approach to reducing calving difficulty is to select heifers with higher breeding value for calving ease. Calving ease is often associated with lower birth weight and that may result in other possible effects on lifetime productivity. Females from experimental select and control calving ease lines within each of the seven populations were compared. Random samples of 720 heifers from lines selected for better calving ease breeding values and 190 heifers from control lines selected for average birth weights were followed through four parities. Select and control lines within the same population were selected to achieve similar yearling weight breeding values. Weights of sampled heifers in select lines were 2.6 kg ( P < 0.01) lighter at birth but not different from control lines at weaning. Select lines had significantly shorter hip height, lighter mature weight, and greater calving success at second parity. Their calves were born significantly earlier with lighter weights and less assistance. Significant interactions with parity showed fewer calves assisted and greater calf survival to weaning as heifers but negligible differences with control lines in later parities. Steer progeny sampled from these dams in select lines ( n = 204) were not different from steers in control lines ( n = 91) for hot carcass weight but had significantly greater fat depth. Two production systems were compared considering the seven populations as replicates. The systems differed in selection history of females (select and control lines) and the use of bulls within their lines as young cows, but used the same bulls in both lines as older cows. Cows were culled after single unsuccessful breeding and kept for up to four parities. Select line cows tended ( P ≤ 0.10) to wean more calves and stay in the herd longer. They were assisted significantly fewer times at calving and had greater calf weight gain to weaning when evaluated over their herd life. Mature weights were lighter in select lines, but marketable cow weight from the systems was nearly identical. Control lines did have more marketable young cow weight and select lines older cow weight. Weaned calf weight per heifer starting the system was significantly greater for the select heifer system due to greater survival of calves from heifers and greater calving success at second parity. No important unfavorable effects of genetic differences in calving ease were identified in this experiment.